Asymmetric information in secondary insurance markets: Evidence from the life settlements market - Daniel Bauer; Jochen Ruß; Nan Zhu (Quantitative Economics, 2020)
We use data from a large US life expectancy provider to test for asymmetric information in the secondary life insurance-or life settlements-market. We compare realized lifetimes for a subsample of settled policies relative to all (settled and nonsettled) policies, and find a positive settlement-survival correlation indicating the existence of informational asymmetry between policyholders and investors. Estimates of the 'excess hazard' associated with settling show the effect is temporary and wears off over approximately 8 years. This indicates individuals in our sample possess private information with regards to their near-term survival prospects and make use of it, which has economic consequences for this market and beyond.
Keywords: D12; G22; J10; 330; Asymmetric information; life settlements; life expectancy; secondaryinsurance market